The Implementation of Dishonorable Discharge for Indonesian National Armed Forces (TNI) Soldiers as a Means of Law Enforcement - Arief Fahmi Lubis (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
To uphold legal principles within the military framework, it is imperative to establish legislative measures that serve as regulatory frameworks for soldiers. These measures are designed to govern their conduct both in the execution of official duties and in the regulation of their involvement within the broader societal context. This research aims to scrutinize the procedural intricacies involved in implementing dishonorable discharge for Indonesian National Armed Forces (TNI) soldiers who engage in criminal activities as a means of upholding the rule of law. Furthermore, it seeks to identify and address the challenges encountered in the process. This study applies a normative juridical approach, specifically descriptive-analytical research. Data comprises both secondary sources (i.e., literature works) and primary sources (i.e., interviews). The presentation of data is structured in a descriptive format, employing a qualitative analytical method. Research findings reveal that the process of implementing dishonorable discharge for TNI personnel involved in criminal activities encompasses both administrative and military disciplinary measures. Challenges encountered in the sanction application include (a) instances of unit commanders’ tardiness in administering administrative penalties and (b) efforts to address these impediments by ensuring meticulous law enforcement within each unit, coupled with conducting awareness campaigns across the entire units in TNI. It is underscored that criminal acts committed by TNI personnel are regarded as breaches of military discipline, carrying the threat of military and disciplinary penalties, alongside administrative sanctions culminating in dismissal. The application of administrative sanctions is anticipated to mitigate violations and instill a deterrent effect among TNI personnel. Legal ramifications persist for the individuals involved until the completion of their service. A proposed solution requires the submission of a comprehensive personality development progress report by respective unit commanders, confirming the completion of all legal processes, thereby facilitating the individual’s seamless career progression.